2013
DOI: 10.1371/journal.pone.0065836
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation Dynamics of the Mistletoe and Its Host in Savanna Areas with Different Fire Occurrence

Abstract: Mistletoes are aerial hemiparasitic plants which occupy patches of favorable habitat (host trees) surrounded by unfavorable habitat and may be possibly modeled as a metapopulation. A metapopulation is defined as a subdivided population that persists due to the balance between colonization and extinction in discrete habitat patches. Our aim was to evaluate the dynamics of the mistletoe Psittacanthus robustus and its host Vochysia thyrsoidea in three Brazilian savanna areas using a metapopulation approach. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Our finding that the probability of mistletoe infection increases with increasing tree size is in accordance with studies from other ecosystems [ 16 , 20 , 35 , 36 ]. Aukema and Martínez del Rio [ 16 ] have found that within one host species, the tallest trees were more likely to be infected because they received more mistletoe seeds than smaller trees due to a higher number of bird visits, which is also likely to be a reason for the higher probability of infection of larger trees in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding that the probability of mistletoe infection increases with increasing tree size is in accordance with studies from other ecosystems [ 16 , 20 , 35 , 36 ]. Aukema and Martínez del Rio [ 16 ] have found that within one host species, the tallest trees were more likely to be infected because they received more mistletoe seeds than smaller trees due to a higher number of bird visits, which is also likely to be a reason for the higher probability of infection of larger trees in our study.…”
Section: Discussionsupporting
confidence: 93%
“…It is known to parasitize 12 host species of Vochysiaceae and two species of Melastomataceae throughout its geographic range (Monteiro et al, 1992;Teodoro et al, 2010;Scalon et al, 2013). Indeed, this species usually presents a clumped distribution on the vegetation and infects the uppermost portions of taller host trees (Teodoro et al, 2010), with the population dynamics directly affected by fire occurrence (Teodoro et al, 2013). This mistletoe is one of the most conspicuous parasitic plant in the landscapes encompassing Rupestrian Grasslands or campo rupestre (CR hereafter), the Brazilian old-growth montane fire-prone vegetation mosaics with remarkable plant diversity and endemism (Silveira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mistletoes may alter host growth, reproduction and physiology, decreasing its fitness (Mourão et al 2009;Bell & Adams 2011). Thin twigs (< 1 cm in diameter) often die when infected by mistletoes (Sargent 1995), as can highly infected hosts (Teodoro et al 2013).…”
Section: Introductionmentioning
confidence: 99%